P&D em filiais de empresas multinacionais instaladas no Brasil - Gomes, Rogério [UNESP]; Consoni, Flavia Luciane; Galina, Simone (My University, 2010)
The internationalization of research and development (R&D) activities has been lifted to an eminent role over the last years, how confirm the greater intensity of R&D investment inflows into countries other than the home countries of the multinational enterprises (MNE). As the industrialization of the Brazilian economy has been marked by the presence of MNE, this paper aims to discuss some characteristics of the Brazilian subsidiaries of foreign MNE concerning R&D activities. To do so, we draw on a comprehensive survey applied to MNE affiliates in Brazil in 2006. It allows us to describe the locally-conducted R&D activities, its specificities and perspectives of future inversions. Among its findings, there are evidences pointing that in Brazil the R&D internationalization the phases of investment in manufactures and in R&D may occur almost simultaneously, depending on the sector s involvement in the globalization process.

A internacionalização das atividades de Pesquisa e Desenvolvimento (P&D) vem ganhando intensidade nos últimos anos, como mostram os investimentos em países que não os de origem das empresas multinacionais (EMNs). Como o processo de industrialização da economia brasileira é historicamente marcado pela presença de EMNs, o propósito deste artigo é caracterizar o comportamento das subsidiárias brasileiras das EMNs estrangeiras em relação à P&D. Para isso, apresentamos resultados de um survey aplicado no ano de 2006 com filiais de EMNs instaladas no Brasil, o qual nos permitiu fazer uma caracterização acerca das atividades de P&D conduzidas localmente, as suas especificidades e as perspectivas de investimentos futuros. Dentre os resultados desse estudo está a constatação de que no Brasil as fases de investimento em manufatura e em P&D podem estar ocorrendo quase em simultâneo, dependendo dos setores envolvidos no processo de globalização.
R & D in multinational companies subsidiaries located in Brazil
Keywords: P&D; Internacionalização da P&D; Transnacionais.; filiais brasileiras de empresa multinacionais